2003
DOI: 10.1016/j.cell.2003.08.008
|View full text |Cite
|
Sign up to set email alerts
|

A CBP Binding Transcriptional Repressor Produced by the PS1/ϵ-Cleavage of N-Cadherin Is Inhibited by PS1 FAD Mutations

Abstract: Presenilin1 (PS1), a protein implicated in Alzheimer's disease (AD), forms complexes with N-cadherin, a transmembrane protein with important neuronal and synaptic functions. Here, we show that a PS1-dependent gamma-secretase protease activity promotes an epsilon-like cleavage of N-cadherin to produce its intracellular domain peptide, N-Cad/CTF2. NMDA receptor agonists stimulate N-Cad/CTF2 production suggesting that this receptor regulates the epsilon-cleavage of N-cadherin. N-Cad/CTF2 binds the transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
409
5
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(442 citation statements)
references
References 44 publications
23
409
5
5
Order By: Relevance
“…In the brain, the epigenetic machinery covers basic phenomena such as differentiation, the preservation of tissue specific transcription profiles, as well as complex processes from synaptic plasticity to learning and memory. 21 Mutations and maladaptations of the epigenetic system on the level of DNA methylation, histone acetylation, and methylation are implied in neuro-developmental 22,23 and neurodegenerative 24,25 contexts, as well as neuropsychiatric diseases 26,27 and drug addiction 28,29 (for a review, see Graff et al 30 ). More specifically, the role of HDACs as regulators of transcription has been identified to be fundamental, and perturbation of acetylation homeostasis is now acknowledged to be a central event in neurologic pathologies.…”
Section: Cerebral Ischemia and Endogenous Tolerancementioning
confidence: 99%
“…In the brain, the epigenetic machinery covers basic phenomena such as differentiation, the preservation of tissue specific transcription profiles, as well as complex processes from synaptic plasticity to learning and memory. 21 Mutations and maladaptations of the epigenetic system on the level of DNA methylation, histone acetylation, and methylation are implied in neuro-developmental 22,23 and neurodegenerative 24,25 contexts, as well as neuropsychiatric diseases 26,27 and drug addiction 28,29 (for a review, see Graff et al 30 ). More specifically, the role of HDACs as regulators of transcription has been identified to be fundamental, and perturbation of acetylation homeostasis is now acknowledged to be a central event in neurologic pathologies.…”
Section: Cerebral Ischemia and Endogenous Tolerancementioning
confidence: 99%
“…Two studies conducted in cellular systems further reported that the overexpression of wild-type PS1 stimulated the transcriptional activity ability of CBP and of p300, while FAD-associated PS1 mutations did not produce this effect [153,154]. However, Marambaud et al [155] described a molecular pathway linking FAD-associated PS1 mutations with increased CBP function in cellular models. Briefly, the authors proposed that FAD mutations inhibit the production of an intracellular peptide N-Cad/CTF2 originally cleaved through wild-type PS1, thereby preventing CBP degradation and resulting in upregulated CREB-mediated transcription.…”
Section: Ad and Related Diseasesmentioning
confidence: 99%
“…It also raises the question as to whether other biochemical impairments or behavioral alterations present in APP V717I transgene mice can be reverted in their double transgenic mice. Regarding that PS1 has pleiotropic roles in brain cell functions, e.g., Notch (Naruse et al, 1998;Song et al, 1999) and N-cadherin (Marambaud et al, 2003) processing, it needs to be answered whether the observed learning deficits of the conditional PS1 knockout mice used in their studies were produced solely by hCTF99, by other PS1-cleaved products, or by the lack of a PS1-dependent physiology.…”
Section: Introductionmentioning
confidence: 99%